Cabin - Preston, Natasha (Naperville, Illinois : Sourcebooks Fire, 2016)
Mackenzie and six of her friends head out to a secluded cabin for fun, but two of them are murdered and since they are all suspects, Mackenzie launches her own investigation, revealing secrets and sins among the original seven friends.
Accelerated Reader AR
106906
Keywords: Murder -- Fiction; Secrets -- Fiction; Deadly sins -- Fiction; Mystery and detective stories; Teenagers -- Juvenile fiction; Serial murderers -- Juvenile fiction; Young Adult Fiction -- Social Themes -- Physical & Emotional Abuse; Young Adult Fiction -- Thrillers & Suspense; Lake District (England) -- Juvenile fiction; England -- Lake District; Young adult works; Juvenile works; Suspense fiction; Thrillers (Fiction); Fiction